Research on the prediction of financial expenditure for the assistance and support of the extremely poor in China - Zhang, Jin (Archives of Business Research, 2020)
Extremely poor people are the most difficult part of the poor in China, and they are also an important part of China's fight against poverty. The policy of assisting and supporting the extremely poor people has played an important role in ensuring the survival and living needs of the extremely poor people in urban and rural areas, and realizing the goal of sharing the development results for the whole people. Since 2015, the assistance and support system for the extremely poor has been disbursed separately, the financial expenditure has increased year by year, from 18.297 billion yuan to 25.930 billion yuan, and the annual financial account expenditure exceeds the budgeted expenditure every year. Therefore, it is urgent to make accurate and reasonable expectation on the financial expenditure of the relief of the extremely poor. Based on the analysis of financial support for the assistance and support of the poorest people from 2008 to 2018, this paper uses the Holt index forecast method to predict the social assistance expenditure for the next five years, and concludes that future financial needs will improve the support and assistance of the special hardship.